2010
DOI: 10.1088/0004-637x/724/1/267
|View full text |Cite
|
Sign up to set email alerts
|

Optical Ifu Observations of the Brightest Cluster Galaxy NGC 4696: The Case for a Minor Merger and Shock-Excited Filaments

Abstract: We present deep optical integral-field spectroscopic observations of the nearby (z ∼ 0.01) brightest cluster galaxy NGC 4696 in the core of the Centaurus Cluster, made with the Wide Field Spectrograph (WiFeS) on the ANU 2.3m telescope at Siding Spring Observatory. We investigate the morphology, kinematics, and excitation of the emission-line filaments and discuss these in the context of a model of a minor merger. We suggest that the emission-line filaments in this object have their origin in the accretion of a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
97
3

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(112 citation statements)
references
References 90 publications
12
97
3
Order By: Relevance
“…B1 in their appendix) for a Case B Hα/Hβ ratio. For values appropriate to active galaxies, however, they obtained results consistent with Farage et al (2010). Similar results have been obtained by other authors (e.g., see references in .…”
Section: Differential Extinctionsupporting
confidence: 89%
See 1 more Smart Citation
“…B1 in their appendix) for a Case B Hα/Hβ ratio. For values appropriate to active galaxies, however, they obtained results consistent with Farage et al (2010). Similar results have been obtained by other authors (e.g., see references in .…”
Section: Differential Extinctionsupporting
confidence: 89%
“…Sparks et al (1989) reported a maximum of 0.4 at the south-western end of the dust lane, based on V -and R-band imaging. On the other hand, Farage et al (2010) estimated a maximum of ∼0.7, 3 ′′ north-west of the nucleus, from the observed Hα/Hβ ratio, and the standard assumption for active galaxies that its intrinsic value is higher than the Case B value, at 3.1. reported maximum extinctions of A V ∼2-2.5 (see fig. B1 in their appendix) for a Case B Hα/Hβ ratio.…”
Section: Differential Extinctionmentioning
confidence: 96%
“…Note that this region only appears annular in ratio maps, while all the line fluxes increase towards the centre, so it is possible this emission component extends over the whole disk, but is not apparent inward of r ∼ 4 kpc where star-formation dominates the Hα flux with a lower N2. In e.g., the elliptical NGC 4696, which has shocks from an ongoing merger but very little star formation (Farage et al 2010), the N2 ratio remains uniformly close to 2.…”
Section: Line Ratiosmentioning
confidence: 97%
“…Line ratios from single-component fits to each spaxel with highest signal-to-noise (>8) are plotted as large black dots and those of signal-to-noise 3-8 as small dots. Pure shock models from an updated version of MAPPINGS III (Sutherland & Dopita 1993;Farage et al 2010;Rich et al 2010) are overlaid, demonstrating that shocks likely contribute to the line ratios of >80% of these spaxels, causing them to fall above the photoionization line in one or more diagnostic plots. The grid includes shock-induced line ratios from shocks with velocities of 100 (yellow, top horizontal grid line), 120, 140, 160, 180, and 200 km s −1 (red, bottom horizontal grid line) and for gas with metallicities log(O/H)+12 of 8.69 (blue, vertical grid line on left in first panel and right in others), 8.69, 8.99, 9.17, and 9.39 (green, opposite vertical grid line).…”
Section: Wifes Analysismentioning
confidence: 99%
“…For example, cloud-cloud collisions (e.g. Savedoff, Hovenier & van Leer 1967), tidally-induced gas streams (McDowell et al 2003;Colina et al 2004;Monreal-Ibero et al 2006, 2010Farage et al 2010;Zakamska 2010), and outflows and galactic winds from AGN or star formation (e.g. Heckman et al 1990; Lehnert & Heckman 1996;Lípari et al 2004;Sharp & Bland-Hawthorn 2010) can all produce radiative shocks to dissipate their kinetic energy (Allen et al 2008).…”
Section: Introductionmentioning
confidence: 99%